Superspace evaluation of the two-loop effective potential for the O'Raifeartaigh model - Abdalla, M. C. B. [UNESP]; Helayel-Neto, J. A.; Nedel, Daniel L.; Senise, Carlos R. [UNESP] (Amer Physical Soc, 2010)
All-order spurion-corrected superpropagators and superfield Feynman rules are employed to systematically compute a two-loop corrected effective potential for the O'Raifeartaigh model, that realizes spontaneous supersymmetry breaking. Though the shifted superpropagators are rather nontrivial, superspace techniques may be suitably extended and confirm their efficacy in computing radiative corrections even when supersymmetry breakdown occurs.